Do genetic factors contribute to the association between birth weight and blood pressure?. Issue 8 (1st August 2001) - Christensen, K; Støvring, H; McGue, M
Abstract : OBJECTIVES: To evaluate whether genetic factors contribute to the association between low birth weight and increased blood pressure among adolescents. DESIGN: Historical cohort study of twin pairs. It was evaluated whether (1) a negative association between birth weight and systolic blood pressure was found in the overall twin sample and (2) whether the intrapair difference in birth weight correlated with the intrapair difference in systolic blood pressure—thereby controlling for the effect of genetic factors (all in monozygotic and on average half in dizygotic pairs). SETTING: The Minnesota Twin Family Study. PARTICIPANTS: 1311 pairs of adolescent twins. MAIN RESULTS: A negative association between birth weight and systolic blood pressure was retrieved in the overall sample. The regression coefficient after controlling for current weight was −1.88 mm Hg/kg (SE 0.61), which corresponds to results from previous studies of singleton adolescents. The regression coefficient fell to −0.64 mm Hg/kg (SE 0.86) when the intrapair analyses were used. The largest reduction was observed among monozygotic twins: from −2.44 mm Hg/kg (SE 0.75) in the overall monozygotic twin sample to −1.06 mm Hg/kg (SE 1.14) in the analyses of the within monozygotic pair differences. CONCLUSION: The association between low birth weight and increased blood pressure later in life is well established. "The fetal programming hypothesis" suggests that the association is caused by intrauterine malnutrition while a new hypothesis "the fetal insulin hypothesis" proposes that genetically determined insulin resistance also contributes significantly to the association. A recent twin study of middle aged twins showed no evidence for an influence of genetic factors while this larger study provides support for the fetal insulin hypothesis: the association between birth weight and blood pressure attenuated among adolescents when genetic factors were controlled. Together this suggests an important contribution of genetic factors to the association between fetal growth and systolic blood pressure in adolescence.